Efficient synthesis of 3-benzoyl Benzo[b]thiophenes and raloxifene via Mercury(II)-Catalyzed cyclization of 2-alkynylphenyl alkyl sulfoxides. Issue 20 (17th May 2018) - Wen, Shi-Ming; Lin, Cheng-Han; Chen, Chin-Chau; Wu, Ming-Jung
Abstract: The unique selective estrogen receptor modulator, Raloxifene (1 ), and antitubulin agent2 were synthesized through the key intermediate, 4-methoxybenzyl 2-bromo-4-methoxyphenyl sulfoxide (6 ), respectively. It was found that compared with the o-sulfanyl aryl bromides, the sulfinyl group at ortho position accelerated the Sonogashira coupling reaction of aryl bromides. Thus, compound6 was coupled with 3, 4, 5-trimethoxyphenyl acetylene, followed by mercury-catalyzed cyclization reaction afford compound2 in 79% overall yield. Raloxifene (1 ) was prepared from compound6 in four steps and 33% overall yield via coupling reaction with 1-trimethylsily-2-(4- tert -butyldimethylsiloxy)phenylethyne, mercury-catalyzed cyclization reaction, alkylation and demethylation. Graphical abstract: